Reflections on the war in the fiction of Erico Verissimo - Santos, Donizeth (Revista de Letras, 2013)
Aversion to violence is a recurring theme in Erico Verissimo’s fiction writing. In his novels there are always voices that rise and denounce the ills caused by it to humans. Among these voices used by the writer to combat it, perhaps the strongest is the female one. Therefore, we present in this article some reflections about the horror of the war, made by some of his main characters: Clarissa, Ana Terra, Bibiana e Maria Valeria. Through them, the writer shows the violent and inhuman side of war, quite unlike the glorious side almost always spread by the official history.